Antibacterial properties and modulation analysis of antibiotic activity of NaCe(MoO4)2 microcrystals. (January 2019) - Moura, J.V.B.; Freitas, T.S.; Cruz, R.P.; Pereira, R.L.S.; Silva, A.R.P.; Santos, A.T.L.; da Silva, J.H.; Luz-Lima, C.; Coutinho, H.D.M.
Abstract: This study reports the antibacterial properties and modulation analysis of antibiotic activity by NaCe(MoO4 )2 microcrystals as well as their structural and morphological characterization. Evaluation of the antibacterial and antibiotic-modulating activity was carried out using the broth microdilution method. The Minimum Inhibitory Concentrations (MICs) of the compounds were expressed as the geometric mean of the triplicate values obtained through the use of Resazurin. Compound concentrations in the plates ranged from 512 to 0.5 μg/mL. Regarding its direct antibacterial activity, NaCe(MoO4 )2 had a MIC ≥ 1024 μg/mL against all studied strains. As for its modulatory effect, it presented synergism with the antibiotic Gentamicin against the S. aureus strain and with Norfloxacin against E. coli, causing a reduction of 75% and 60%, respectively, in the antibiotic quantity required to have the same effect on the strain in study.